Potential of ultraviolet laser pulse-induced current for characterizing the grain size of table sugar - Xuecong Liu; Kun Zhao; Xinyang Miao; Honglei Zhan (Heliyon, 2023)
In this work, we proposed a laser-induced current (LIC) method to investigate the grain-size dependence of the plasma of table sugar induced by a nanosecond (ns) pulsed ultraviolet laser in the size range of <180 μm–>550 μm and achieve the lower power consumption in measurement. Under multiple laser irradiations and an external electric field (Vb) of 200 V, the LIC variation's (ΔIp) standard deviation and variance were 0.53 nA and 0.05 nA, respectively, indicating the relatively small systematic error during the testing process. The Vb causes a decrease in the possibility of electron–ion complexation and accelerates the separation, resulting in an increase in ΔIp with Vb. With increasing grain size (diameter D) of table sugar, ΔI demonstrate a valley-like behaviour and 250–380 μm is the critical range Dc where ΔI is very weak and considerably depends on the Vb with the slope of 0.031 nA/V. At D > 550 μm and Vb = 5 V, ΔI intensities monotonically rise by 30 % when D surpasses Dc. In this instance, the energy was the main contributor to the LIC signal during plasma generation and expansion. While D is less than Dc, ΔIp increases by 27 % at D ≤ 180 μm and Vb = 5 V. The yield stress is the main reason for the formation of plasma with high temperature and density in this situation because the sugar behaves like an elastic solid. The reason for such a LIC variation trend was discussed, which can be explained by considering the morphological, thermal and mechanical properties competing with each other. The present result suggests that the LIC method enables non-contact characterisation of sugar particle size at low-power consumption.